Resistance of Upland NERICAs and Parents to Rice Weevil and Angoumois Grain Moth - Santos, C.; Agbangla, C.; Chougourou, D.; Togola, A.; Cisse, B.; Akintayo, I.; Nwilene, F.E. (Science Alert, 2014)
Twenty one rice varieties including 18 upland NERICAs and their parents (two Oryza sativa and one O. glaberrima) were screened for resistance to two primary storage pests: Sitophilus oryzae and Sitotroga cerealella, using the “no choice” infestation method. Resistance of rice varieties was assessed based on the adult’s population obtained from first generation of each species and also on the weight loss recorded on infested samples. Results revealed that adult progenies from S. oryzae and weight loss were very low on paddy and fairly high on husked rice. Results also suggested that glumes are one main parameter conferring the resistance to S. oryzae. Differential responses of rice varieties to S. cerealella were observed. Of the 18 NERICA tested, NERICA6, 14, 4, 3, 15 and 16 were tolerant in increasing order, whereas only NERICA9 and 11 were susceptible. The Oryza glaberrima parent CG 14 was resistant to the insect while the O. sativa parents WAB 56-50 and WAB 56-104 were susceptible. Progenies resistance to the insect may have been provided by the parent CG 14. The implications of the findings and the way forward were discussed.